On a red light - Iceland's financial crisis and the Nordic experience - Mixa, Már Wolfgang; Sigurjónsson, Þröstur Olaf (Research in applied business and economics, 2010)
Academics have in recent years compared financial crises in order to gain a better understanding of preceding circumstances. This paper explores whether Icelanders were oblivious to historical warning signals preceding the financial crisis in 2008. A specific focus is on whether Icelanders should have seen warning signals by exploring warning signs in other countries that have recently dealt with financial crises. This research compares the prelude of Iceland’s financial crisis to preceding circumstances of the Scandinavian crisis during the early 1990s. The result is that the characteristics showed remarkable similarities indicating that a deep crisis was brewing in Iceland. Classic symptoms of a prelude to a crisis were even more evident in Iceland. Á síðustu árum hafa fræðimenn borið saman fjármálakreppur til að skilja betur þær aðstæður sem myndast í undanfara kreppu. Þessari grein er ætlað að varpa ljósi á það hvort Íslendingar flutu sofandi að feigðarósi í aðdraganda fjármálakreppunnar árið 2008. Viðfangsefnið beinist að því hvort Íslendingar hefðu átt að sjá viðvörunarmerkin með því að líta til reynslu annarra landa sem nýlega höfðu glímt við fjármálakreppu. Rannsókn þessi ber undanfara íslensku fjármálakreppunnar saman við undanfara norrænu kreppunnar í upphafi tíunda áratugarins. Niðurstaðan er sú að einkennin voru afar lík og það gaf tilefni til að ætla að djúp kreppa væri í aðsigi á Íslandi. Sígild merki um undanfara kreppu sáust jafnvel enn skýrar á Íslandi.